(untitled) (Conference on English Language Teaching, 2023)
Grammar is considered challenging for EFL students in learning English. The teaching method used by lecturers in English teaching-learning is an essential factor in which students become enjoy or even not interested in learning grammar. Some lecturers often choose conventional techniques and repetition in teaching grammar. This research aimed to determine if there is any significant effect of integrating ICT of the British Council website on the EFL students’ grammar mastery at STKIP PGRI Pacitan in the academic year 2022/2023. A pre-experimental design was conducted in this research. With purposive sampling, they were 25 EFL students as the research subject. Before collecting the data, the researchers previously gave a grammar test as the main instrument before they were given treatment. Then after giving the treatment, a post-test was held. As the secondary one, the researchers used questionnaires. The research findings showed that it was obtained that Sig. (2-tailed) of the equal variance was 0.000 and α = 0.05. The result of Ha is accepted if Sig. (p-value) < α = 0.05, and Ho is rejected. As the final computation, the researchers concluded that there was any significant influence in integrating the ICT of the British Council website on the EFL students’ grammar. Besides, most of the EFL students responded to positive views as their challenge to integrating ICT in the grammar teaching-learning process